2018
DOI: 10.2218/ijdc.v13i1.631
|View full text |Cite
|
Sign up to set email alerts
|

Complexities of Digital Preservation in a Virtual Reality Environment, the Case of Virtual Bethel

Abstract: The complexity of preserving virtual reality environments combines the challenges of preserving singular digital objects, the relationships among those objects, and the processes involved in creating those relationships. A case study involving the preservation of the Virtual Bethel environment is presented. This case is active and ongoing. The paper provides a brief history of the Bethel AME Church of Indianapolis and its importance, then describes the unique preservation challenges of the Virtual Bethel proje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…] the diversity of platforms used to run the environment and render the content for user experiences (web VR, mobile VR, and full head mounted display [HMD] technology), the variety of media types, the multi-layered data structure, and the complexity of relationships among data A related challenge identified is the problem of dependency on proprietary, blackboxed software in which the processing of data is not available to scrutiny by the researcher, and the file formats are supported by only one or two software vendors (Hall et al, 2019). This impacts the transparency and reproducibility of content created for use in VR experiences (Alliez et al, 2017;Meyerson, 2019;Murillo et al, 2018).…”
Section: Challenges Of Preserving Virtual Realitymentioning
confidence: 99%
See 1 more Smart Citation
“…] the diversity of platforms used to run the environment and render the content for user experiences (web VR, mobile VR, and full head mounted display [HMD] technology), the variety of media types, the multi-layered data structure, and the complexity of relationships among data A related challenge identified is the problem of dependency on proprietary, blackboxed software in which the processing of data is not available to scrutiny by the researcher, and the file formats are supported by only one or two software vendors (Hall et al, 2019). This impacts the transparency and reproducibility of content created for use in VR experiences (Alliez et al, 2017;Meyerson, 2019;Murillo et al, 2018).…”
Section: Challenges Of Preserving Virtual Realitymentioning
confidence: 99%
“…In their study of multiple stakeholders interested in VR preservation, Hardesty et al (2020, p. 17) found that "it is difficult to decouple the digital content from the hardware requirements and that the necessity of capturing hardware and environment is not adequately represented in the [existing digital curation] model." Current attempts to preserve materials related to VR projects (Moore et al, 2019;Murillo et al, 2018;Richards-Rissetto and von Schwerin, 2017) have focused primarily on the archiving and preservation needs of the VR content files (e.g. 3D data, 3D models, Unity3D project files, executable VR files and other assets).…”
Section: Disrupting Archival Thinkingmentioning
confidence: 99%